1968
DOI: 10.1063/1.1656118
|View full text |Cite
|
Sign up to set email alerts
|

High Photovoltages in Cadmium Sulfide Films

Abstract: Larger-than-bandgap photovoltages were observed in thin films of CdS which had high resistances and were not uniformly thick. The decay of the photovoltage after removal of light and the effects of temperature and light intensity on the photovoltage were studied and compared to a theoretical model. The results conform with the concept that the photovoltage is due to a space charge produced by a nonuniform distribution of trapped carriers in a multitude of series-connected elements. Analysis of the decay of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1970
1970
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It is a straight line which shows log͑V och ͒ increases linearly with 1000/ T and implies that V och increases exponentially with 1000/ T. Such a behavior of V och with temperature was observed by Brandhorst and Potter 13 in Si and SiC films above room temperature ͑T Ͼ 333 K͒. In some Si films 13 they observed that V och increased more slowly with 1000/ T as the temperature was lowered below T Ͻ 333 K. However, in CdS films 10 and in one silicon film, 13 they found that V och increased with 1000/ T for a decrease of temperature and showed a peak at ϳ250 K and then decreased rapidly with 1000/ T for T Ͻ 250 K. In Cd 3 As 2 films, Zdanowicz et al 22 had also observed a small peak of height 35 V in the V och vs 1000/ T curve at ϳ240 K followed by a dip at 230 K and then a regular increase of V och with 1000/ T for 230 K Ͼ T Ͼ 90 K. However, after storing the film for 2 days they observed a big peak of height 140 V at ϳ200 K that was followed by a sharp decrease with 1000/ T such that V och was reduced to zero at 143 K and changed polarity for T Ͻ 143 K. After storage of 3 months, films showed a still higher peak of 200 V corresponding to T = 220 K which was followed by a sharp decrease with 1000/ T such that V och again became zero at 1000/ T =9 ͑i.e., for T = 110 K͒ and changed its polarity for T Ͻ 110 K. These Cd 3 As 2 films had been given a SiO x coating on the film surface. We have plotted curve 2 for the 400 K Ͼ T Ͼ 80 K temperature range in Fig.…”
Section: Intensity Dependence Of V Ochmentioning
confidence: 87%
See 4 more Smart Citations
“…It is a straight line which shows log͑V och ͒ increases linearly with 1000/ T and implies that V och increases exponentially with 1000/ T. Such a behavior of V och with temperature was observed by Brandhorst and Potter 13 in Si and SiC films above room temperature ͑T Ͼ 333 K͒. In some Si films 13 they observed that V och increased more slowly with 1000/ T as the temperature was lowered below T Ͻ 333 K. However, in CdS films 10 and in one silicon film, 13 they found that V och increased with 1000/ T for a decrease of temperature and showed a peak at ϳ250 K and then decreased rapidly with 1000/ T for T Ͻ 250 K. In Cd 3 As 2 films, Zdanowicz et al 22 had also observed a small peak of height 35 V in the V och vs 1000/ T curve at ϳ240 K followed by a dip at 230 K and then a regular increase of V och with 1000/ T for 230 K Ͼ T Ͼ 90 K. However, after storing the film for 2 days they observed a big peak of height 140 V at ϳ200 K that was followed by a sharp decrease with 1000/ T such that V och was reduced to zero at 143 K and changed polarity for T Ͻ 143 K. After storage of 3 months, films showed a still higher peak of 200 V corresponding to T = 220 K which was followed by a sharp decrease with 1000/ T such that V och again became zero at 1000/ T =9 ͑i.e., for T = 110 K͒ and changed its polarity for T Ͻ 110 K. These Cd 3 As 2 films had been given a SiO x coating on the film surface. We have plotted curve 2 for the 400 K Ͼ T Ͼ 80 K temperature range in Fig.…”
Section: Intensity Dependence Of V Ochmentioning
confidence: 87%
“…The spectral response of photovoltage was of an inverted-V shape with a peak at ϳ500 nm wavelength. 10 Photovoltage varied linearly with intensity up to 50 mW/ cm 2 but increased at a smaller rate between 50 and 150 mW/ cm 2 intensity. 10 In CdS films 10 and also in a Si film, 13 the photovoltage increased with the decrease in temperature from 330 to ϳ230 K and then decreased with further lowering of the temperature.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations